Delegation, time inconsistency and sustainable equilibrium - Henrique S. Basso (Uppsala University, Department of Economics, 2008)
This paper analyzes the effectiveness of delegation in solving the time inconsistency problem of monetary policy using a microfounded general equilibrium model where delegation and reappointment are explicitly included into the government's strategy. The method of Chari and Kehoe (1990) is applied to characterize the entire set of sustainable outcomes. Countering McCallum's (1995) second fallacy, delegation is able to eliminate the time inconsistency problem, with the commitment policy being sustained under discretion for any intertemporal discount rate.
urn:nbn:se:uu:diva-86982
Keywords: E52; E58; E61; 330; Central Bank; Monetary Policy; Institutional Design; Zentralbank; Geldpolitisches Ziel; Zeitkonsistenz; Allgemeines Gleichgewicht